The role of strategic leadership and Internet of Things monitoring on organisational performance with innovative work behaviour as a moderator at PTPN IV Regional III-Riau - Iskandar Iskandar; Marnis Marnis; Machasin Machasin (Journal of Applied Business Administration, 2026)
PTPN IV Regional III is a state-owned enterprise where this research was conducted, operating in Riau to produce palm oil and palm kernel. In this study, Organisational Performance refers to the performance of the palm oil mill, measured by the achievement of palm oil yield from fresh fruit bunches in the nucleus plantation. Strategic Leadership refers to all decisions and policies made by senior employees regarding factory operations. IoT Monitoring is supervision with digital output via the Internet of Things (IoT), focused on factory processes, with Innovative Work Behaviour as a moderating variable. This study used SEM WarpPLS analysis. Respondents to the questionnaire were all senior employees involved in factory operations, located at the Head Office, District Offices, and factories of PTPN IV Regional III, for a total of 102 people. The results of this study conclude that Strategic Leadership and IoT Monitoring have a positive and significant effect on Organisational Performance. Strategic Leadership and IoT Monitoring have a significant effect on Organisational Performance, moderated by Innovative Work Behaviour.